Religiosity and Mental Health: A Contribution to Understanding the Heterogeneity of Research Findings - Malinakova, Klara; Tavel, Peter; Meier, Zdenek; van Dijk, Jitse P; Reijneveld, Sijmen A (International journal of environmental research and public health, 2020)
Most studies report positive associations between religiosity and spirituality and aspects of mental health, while a small proportion report mixed or fully negative associations. The aim of this study was to assess the associations of religiosity measured more specifically, with mental health in a secular environment, using a nationally representative sample of Czech adults (n = 1795). We measured religious affiliation, conversion experience, non-religious attitudes and the stability of these attitudes, mental health problems, and anxiety levels. Compared to stable non-religious respondents, unstable non-religious and converted respondents who perceived God as distant were more likely to experience anxiety in close relationships, and had higher risks of worse mental health. Our findings support the idea that the heterogeneity of findings in associations between religiosity/spirituality and mental health could be due to measurement problems and variation in the degree of secularity. A shift towards religiosity could be expected to be seen in a substantial part of non-religious respondents in problematic times.
Keywords: Young Adult; Male; mladý dospělý; Attitude; Adolescent; Česká republika; measurement; Mental Health; Adult; Aged; dospělí; duševní zdraví; mužské pohlaví; senioři; Religion; religiosity/spirituality; mladiství; Czech Republic; mental health; senioři nad 80 let; náboženství; lidé; ženské pohlaví; Humans; attachment; postoj; Aged, 80 and over; atheism; Female; lidé středního věku; Middle Aged